Problem-Based E-Modules Using Flipbooks as a 21st Century Learning Innovation - Rahmawati, Indah; Mukniah, Mukniah; Sahlan, Moh (SAINTIS Publishing, 2025)
The rapid development of digital technology has driven the emergence of more interactive learning innovations that are adaptive to the needs of the 21st century. One such innovation is the problem-based e-module presented in flipbook format. This study aims to examine the concept, characteristics, and urgency of using flipbook-based e-modules in enhancing 21st-century skills. The research employed a descriptive qualitative approach through library research by analyzing various literature, scientific articles, and educational policy documents related to e-modules, problem-based learning (PBL), and flipbook media. The findings indicate that problem-based e-modules provide more contextual learning experiences, position students as active subjects, and encourage the mastery of critical thinking and problem-solving skills. The integration of flipbooks as interactive media enhances the attractiveness, flexibility, and effectiveness of learning, thereby motivating students to learn more independently. Thus, problem-based e-modules using flipbooks can be considered an innovative strategy aligned with the demands of 21st-century education while supporting the transformation of digital technology-based learning.